A Path Analysis Model for Explaining the Factors Influencing Wearing a Mask among Commuting Workers Using Commuter Line Bogor-Jakarta - Kusmawan, David; Andari, Shofi; Gustina, Ira; Susilowati, Indri Hapsari; Wirawan, Mufti (Kesmas, 2021)
Jakarta is one of the most air-polluted cities in the world, which can increase the health risk of commuting workers exposed to pollutants. This study aimed to determine the factors that directly and indirectly affect healthy behavior (wearing a mask) for commuters using the Bogor-Jakarta Commuter Line. Furthermore, a total of 155 respondents participated and the data collected were analyzed using descriptive and path analysis. The commuters aware of the hazard potential related to air pollution during commuting were 137 people (88.4%). While 104 people (67.1%) were aware of the good perception of pollution and 125 uses masks during commuting (80.6%). The healthy behavior in commuting workers using Commuter Line was affected by some factors, both directly and indirectly. The knowledge and commuting experience toward healthy behavior were two variables that significantly influenced on healthy behavior. The knowledge was also the only mediated variable with a significant indirect effect of education on healthy behavior.